CORPORATE GOVERNANCE AND FINANCIAL POLICY IN DETERMINING THE COST OF DEBT - Mardianto Hasudungan Marpaung; Jonris Hotman Tua (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
This study examines the role of corporate governance and financial policy in determining firms’ cost of debt. Specifically, the research investigates the impact of board size as a governance mechanism and leverage as a financial policy indicator on the cost of debt. Effective corporate governance is expected to reduce agency conflicts and information asymmetry between firms and creditors, thereby lowering borrowing costs. At the same time, financial policy decisions such as leverage may influence the level of financial risk perceived by lenders. Using panel data from publicly listed companies, this study employs regression analysis to evaluate the relationship between board size, leverage, and the cost of debt while controlling for firm size, profitability, and sustainable growth rate. The empirical results indicate that board size is negatively associated with the cost of debt, suggesting that firms with larger boards benefit from stronger monitoring mechanisms that enhance creditor confidence and reduce borrowing costs. In contrast, leverage is found to have a positive and statistically significant effect on the cost of debt, indicating that higher debt levels increase perceived financial risk and lead to higher borrowing costs. These findings support the predictions of agency theory and capital structure theory, highlighting the importance of governance mechanisms and prudent financial policies in shaping firms’ financing conditions. The study contributes to the literature on corporate governance and corporate finance by providing empirical evidence on how governance structures and capital structure decisions influence borrowing costs. The results also provide practical implications for managers and policymakers seeking to improve governance practices and maintain sustainable financial policies to reduce firms’ financing costs.